Cardiotoxicity Associated with the Tyrosine Kinase Inhibitor Sunitinib - Chu, Tammy F. (2007)
BACKGROUND: Tyrosine kinase inhibitors (TKIs) have advanced cancer treatment. Sunitinib, a recently-approved, multi-targeted TKI, prolongs survival for patients with metastatic renal cell carcinoma (RCC) and gastrointestinal stromal tumor (GIST), but concerns about cardiac safety have arisen with this agent. METHODS: To determine the cardiovascular risk associated with sunitinib, we reviewed all cardiovascular events in patients with imatinib-resistant, metastatic GIST at the Dana-Farber Cancer Institute enrolled in a Phase I/II protocol evaluating the efficacy of the drug (n=75). Sunitinib’s effects on left ventricular ejection fraction (LVEF) and blood pressure (BP) were also examined. Studies in isolated cardiomyocytes and mice investigated potential mechanisms of sunitinib-associated cardiac effects. FINDINGS: Eleven percent (8/75) of subjects suffered a cardiovascular event with congestive heart failure (CHF) occurring in 8% (6/75) of the population. Twenty-eight percent (10/36) of patients treated at the FDA-approved dose had LVEF declines of ≥ 10 EF%, and nineteen percent (7/36) experienced LVEF declines of ≥ 15 EF%. Sunitinib induced significant increases in mean systolic and diastolic BP in patients, and 47% (35/75) of individuals developed hypertension (HTN) (>150/100 mmHg). CHF and LV dysfunction generally responded to withholding drug and instituting medical management. In mice and cultured cardiomyocytes, sunitinib caused mitochondrial injury and cardiomyocyte apoptosis. INTERPRETATION: Sunitinib treatment can lead to HTN, LVEF decline, and/or CHF. Experimental studies suggest that this is due, at least in part, to direct cardiomyocyte toxicity which may be exacerbated by HTN. Patients treated with sunitinib should receive close monitoring and prompt treatment for HTN and/or LVEF decline.